Islam & Europe : Challenges and Opportunities - Abicht, Ludo (Book collections on Project MUSE., 2008)
"Seven well-known influential authorities - each an active participant in the public debate on the global role of Islam past, present and future - recently presented papers at the first Intercultural Relations Conference sponsored by Forum A. & A. Leysen. These important contributions, on the topic Islam & Europe: Challenges and Opportunities, are presented in this volume." "Although each contributor speaks from his own distinctive point of view, a common message emerges from all seven texts. Only dialogue - between the West and Islam on the one hand, and within and among societies historically identified with Islam on the other - will overcome entrenched confrontation and negative animosity, and engender new possibilities and understandings. By encouraging free and critical drinking, dialogue paves the way to social equity and the scientific innovation that, potentially, can lead to more prosperity. In the course of the conference all seven talks led to fascinating debates. This book includes the most important questions asked and the speakers' responses. Although the question of how to actually construct the dialogue remains unsettled, this ground-breaking book takes a giant step toward an answer"--Jacket